The Implementation of Asynchronous learning in University during the Covid-19: What Do Students Think? - Selviana Napitupulu (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study sought to understand students' perceptions on asynchronous learning implementations (Camtasia Studio and Google-Classroom) during Covid-19, to identify the benefits and drawbacks of these tools, and to assess how much students trusted this type of learning when it was used in a rural setting. 45 respondents from the English Education Study Program made up the study's subject. It happened in the second, fourth, sixth, and eighth semesters. This study used a qualitative descriptive design. The data was gathered via a questionnaire, open-ended questions, and interviews. The study's findings suggested that these platforms had encountered a number of difficulties. Limited internet connectivity, according to more than half of respondents, was one of the biggest obstacles to implementing asynchronous learning (Camtasia Studio and Google Classroom apps). Despite some limitations in their online course, Camtasia Studio and Google Classroom offer greater benefits. Many of the respondents thought that their advantages outweighed their limitations. The majority of respondents believed that it helped EFL students improve their language learning, particularly in their writing abilities, and that it might also help students' ICT skills.